Managing sleep apnea: long-term outcomes from a comprehensive, patient-centered treatment care pathway - Riney, Heidi Doss; Thorndike, Frances P.; Agustsson, Jon S.; Helgason, Snorri; Hauser, Karina; Baran, Alp Sinan; Kauss, Thomas; Salinas, Gregory David; Edington, Samantha; Wickwire, Emerson M. (Frontiers in Sleep, 2025)
IntroductionObstructive Sleep Apnea (OSA) is a chronic disease requiring life-long care, with clear benefit for those who remain adherent to positive airway pressure (PAP) therapy. Despite the efficacy of PAP, adherence to treatment has historically been low. The purpose of this study was to determine the impact of a streamlined OSA care pathway on quality of care and PAP adoption/adherence.MethodsTwo retrospective cohort studies were performed based on real-world data gathered as part of routine clinical care within a large comprehensive sleep care program. In Study 1, quality of OSA care was assessed by evaluating days spent between treatment steps of the care pathway, including time to diagnosis and treatment initiation. In Study 2, long-term PAP adoption, adherence, and persistence data were analyzed; PAP average minutes used per night and average nights per week were also calculated.ResultsIn Study 1, patients (n = 42,687) typically underwent telehealth consultation within 5 days of OSA screening; completed Home Sleep Apnea Testing (HSAT) within 12 days from physician consultation; received testing results and recommendations within 9 days of completing HSAT; and initiated PAP within 8 days of a diagnosis. In Study 2 (N = 4,907), 84.3% of patients placed on therapy adopted therapy and 80.6% of those who adopted demonstrated short-term adherence. 82.6% of patients demonstrated long-term PAP adherence 1 year after adoption and 74.2% of patients persisted with PAP 2 years after adoption. PAP usage rates increased over time. By year 3, patients (n = 3,067) used their PAP device an average of 6.0 days per week, with mean usage of 6.4 h per night.DiscussionLength of time between treatment steps was shorter than published reports. Rates of both short- and long-term adherence and persistence to PAP therapy were also higher than those observed in most prior studies. Average nightly use and nights per week used trend upward across the 3 years. These findings suggest that a comprehensive OSA care approach can effectively help more patients get on therapy and stay on therapy, providing an opportunity for the health and economic benefits reported in the literature.